Application of exopolysaccharide produced by chlorella vulgaris as adjuvant for mannheimia haemolytica a2 vaccine in goat - Insyirah husna binti kamaradin (Universiti Malaysia Terengganu, 2022)
Pneumonic mannheimiosis is a common respiratory disease among small ruminants caused by Mannheimia haemolytica A2. Presently, the most efficient and costeffective mean of protection against this disease is through proper intranasal vaccination but the commercially available vaccines shown poor immunogenicity responses, or low protection level. Therefore, improving the vaccine via stimulating greater immune response requires incorporation of adjuvant. This study measures the potential of exopolysaccharide (EPS) extracted from Chlorella vulgaris as an adjuvant vaccine that can trigger the humoral and cellular immune response in both mucosal and systemic immunity against M. haemolytica A2 infection. Initially, prior to formation of Exopolysaccharide- M. haemolytica A2 (EPS-MHA2) vaccine, tests conducted to verify EPS’s characteristics which include using of Gel Permeation Chromatography (GPC) shown its molecular weight of 2398 Da. Its typical signals for polysaccharides were detected by Fourier Transform Infrared Spectra (FTIR). Scanning Electron Microscope (SEM) displayed the compact microstructure of EPS surface view while cytotoxicity test proved EPS nontoxicity. Subsequently, the potentiality of EPS-MHA2 as adjuvanted vaccine was put to pre-clinical test on white rats to determine its ability to enhance and stimulate immune response, which indicated by the significant high-level production of antibody (IgM, IgG and IgA) in blood serum of Sprague Dawley.